Have Alcohol Management Plans Reduced Violence Against Women in Cape York, Australia?. (November 2018) - West, Caryn; Muller, Reinhold; Clough, Alan R.; Fitts, Michelle S.
In 2002/2003, the Queensland Government released a decision that Alcohol Management Plans (AMPs) were to be introduced to most Indigenous communities in Cape York, Australia, in an effort to address violence generally and specifically violence against women and children. By 2008, increased restrictions brought total prohibition in some communities and tightened restrictions in others. This project provides a pre-/postprohibition comparison and analysis of injuries, injuries that involved alcohol and verified police reported assaults. Supporting this are rich community survey data which together aim to elicit the effect restricting alcohol had on violent activity in the communities, particularly for women.